Preventing acute neurotoxicity of CNS therapeutic oligonucleotides with the addition of Ca2+ and Mg2+ in the formulation - Miller, Rachael; Paquette, Joseph; Barker, Alexandra; Sapp, Ellen; McHugh, Nicholas; Bramato, Brianna; Yamada, Nozomi; Alterman, Julia; Echeveria, Dimas; Yamada, Ken; Watts, Jonathan; Anaclet, Christelle; et al. (bioRxiv, 2024)
Oligonucleotide therapeutics (ASOs and siRNAs) have been explored for modulation of gene expression in the central nervous system (CNS), with several drugs approved and many in clinical evaluation. Administration of highly concentrated oligonucleotides to the CNS can induce acute neurotoxicity. We demonstrate that delivery of concentrated oligonucleotides to the CSF in awake mice induces acute toxicity, observable within seconds of injection. Electroencephalography (EEG) and electromyography (EMG) in awake mice demonstrated seizures. Using ion chromatography, we show that siRNAs can tightly bind Ca2+ and Mg2+ up to molar equivalents of the phosphodiester (PO)/phosphorothioate (PS) bonds independently of the structure or phosphorothioate content. Optimization of the formulation by adding high concentrations (above biological levels) of divalent cations (Ca2+ alone, Mg2+ alone, or Ca2+ and Mg2+) prevents seizures with no impact on the distribution or efficacy of the oligonucleotide. The data here establishes the importance of adding Ca2+ and Mg2+ to the formulation for the safety of CNS administration of therapeutic oligonucleotides.Oligonucleotide therapeutics (ASOs and siRNAs) have been explored for modulation of gene expression in the central nervous system (CNS), with several drugs approved and many in clinical evaluation. Administration of highly concentrated oligonucleotides to the CNS can induce acute neurotoxicity. We demonstrate that delivery of concentrated oligonucleotides to the CSF in awake mice induces acute toxicity, observable within seconds of injection. Electroencephalography (EEG) and electromyography (EMG) in awake mice demonstrated seizures. Using ion chromatography, we show that siRNAs can tightly bind Ca2+ and Mg2+ up to molar equivalents of the phosphodiester (PO)/phosphorothioate (PS) bonds independently of the structure or phosphorothioate content. Optimization of the formulation by adding high concentrations (above biological levels) of divalent cations (Ca2+ alone, Mg2+ alone, or Ca2+ and Mg2+) prevents seizures with no impact on the distribution or efficacy of the oligonucleotide. The data here establishes the importance of adding Ca2+ and Mg2+ to the formulation for the safety of CNS administration of therapeutic oligonucleotides.